Study of microflora in malaysian dried fishes and their decontamination by gamma-irradiation - Ito, Hitoshi; Yusop Abu, Mohd (Oxford University Press (OUP), 1985)
The distribution of microorganisms in 10 samples of salted dried fish and the effects of irradiation of them were studied. The total aerobic bacteria in commercial dried fish were determined to be from 2 x 104 to 3 x 106 per gram. Mold counts were 1 x 102 to 7 x 103 per gram with a lower amount of yeasts. In spoiled dried fish, total aerobic bacteria were determined to be 4x 106 or lx 107 per gram with a few yeasts. Coliforms were not isolated on MacConkey agar plates from any of the samples. The predominant bacteria occurring in spoiled dried fish were Pediococcus halophilus, Vibrio costicola and Planococcus sp. More than 50% of the molds consisted of the Aspergillus niger group, whereas lower amounts of the A. flavus, A. fumigatus and A. ochraceus groups, Penicillium chrysogenum series, etc. were also isolated from many samples of dried fish. All kinds of putrefactive microorganisms were radiation sensitive, and a dose of ca. 500 krad appears to be sufficient for extension of the shelf-life of dried fish from 2 to 4 times.